The relationship between the mode of presentation, CT‐derived body composition, systemic inflammatory grade and survival in colon cancer. Issue 6 (11th October 2022) - Golder, Allan M.; Sin, Ling Kwan Ernest; Alani, Fatima; Alasadi, Ala; Dolan, Ross; Mansouri, David; Horgan, Paul G.; McMillan, Donald C.; Roxburgh, Campbell S.
Abstract: Background: Within colorectal cancer, the systemic inflammatory response (SIR) and CT‐derived body composition, particularly the loss of lean muscle mass, are independently associated with oncological outcomes; however, no study has included both non‐metastatic and metastatic disease. The present study analyses the association between body composition, mode of presentation, SIR and survival in patients with TNM I–IV colon cancer. Methods: Patients diagnosed with colon cancer from 2011 to 2014 were identified. The SIR was stratified using systemic inflammatory grade (SIG). Staging CT scans were used to define body composition: subcutaneous fat index (SFI), visceral fat area (VFA), skeletal muscle index (SMI) and skeletal muscle density (SMD). The effect of SIG and body composition on mode of presentation and 3‐year overall survival (3‐yr OS) was analysed. Results: One thousand one hundred forty‐six patients were identified; 14%/38%/40%/8% had TNM Stage I/II/III/IV colon cancer, respectively. Patients were predominantly aged 65 + (63%), male (52%) and BMI > 25 (62%). 79%74% had a high SFI/VFA, and 56%/62% had a low SMI/SMD, respectively. Abnormal body composition was prevalent across all disease stages and associated with TNM stage—high SFI in 87%/76%/81%/68% ( P  < 0.001), high VFA in 79%/73%/75%/67% ( P  = 0.189), low SMI in 43%/60%/55%/68% ( P  < 0.001) and low SMD in 55%/65%/61%/67% ( P  = 0.094) of TNM I/II/III/IV disease, respectively. Body composition was associated with SIG—high SFI in 83%/80%/77%/78%/66% ( P  = 0.004), high VFA in 78%/78%/70%/63%/61% ( P  = 0.002), low SMI in 48%/52%/62%/62%/79% ( P  < 0.001) and low SMD in 56%/60%/62%/70%/76% ( P  < 0.001) of patients with SIG 0/1/2/3/4, respectively. After adjustment for other factors, increased SIG (OR 1.95), visceral obesity (OR 0.65) and low SMI (OR 1.61) were associated with emergency presentation. In TNM Stage II colon cancer, low SMI and low SMD were associated with worse 3‐yr OS (92% vs 87%, P  < 0.001 and 96% vs 85%, P  < 0.001, respectively). In TNM Stage III, a trend was seen between low SMI and SMD and 3‐yr OS (77% vs 73%, P  = 0.091 and 76% vs 75%, P  = 0.034, respectively). In TNM Stage IV disease, low SMI was associated with 3‐yr OS (43% vs 16%, P  < 0.001). A trend, albeit not of significance, was seen between low SMD and 3‐yr OS (32% vs 21%, P  = 0.366). Conclusions: The present results show that abnormal body composition is prevalent across TNM I–IV colon cancer and associated with TNM stage and SIG. Body composition is independently associated with emergency presentation and long‐term survival. Further research is required to analyse whether interventions including structured exercise programmes or attenuation of the SIR have an effect on CT‐derived body composition and oncological outcomes.